2023
DOI: 10.1111/joa.13876
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean tongue mobility and function: A comparative review

Abstract: Cetaceans are atypical mammals whose tongues often depart from the typical (basal) mammalian condition in structure, mobility, and function. Their tongues are dynamic, innovative multipurpose tools that include the world's largest muscular structures. These changes reflect the evolutionary history of cetaceans' secondary adaptation to a fully aquatic environment. Cetacean tongues play no role in mastication and apparently a greatly reduced role in nursing (mainly channeling milk ingestion), two hallmarks of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 284 publications
0
5
0
Order By: Relevance
“…These hydrodynamic effects could also slightly diminish pressures where water enters at the anterior of the mouth, perhaps not sufficiently to generate truly notable subambient suction pressures, but at least enough to obviate an anterior compressive bow wave that might physically disperse small prey and/or warn them of an approaching whale. Flow experiments (Werth, 2004, Werth, 2013 using pressure transducers and videorecording of particles and prey (Werth, 2012) have confirmed that these limited yet real pressure effects in laboratory settings (Figure 7), and tantalizing photographs and video recordings of whales foraging at sea (Werth and Potvin, 2016;Werth and Crompton, 2023) have likewise supported conclusions of Bernoulli and Venturi effects.…”
Section: Flow-dependent Porosity Determined By Varying Parametersmentioning
confidence: 58%
See 4 more Smart Citations
“…These hydrodynamic effects could also slightly diminish pressures where water enters at the anterior of the mouth, perhaps not sufficiently to generate truly notable subambient suction pressures, but at least enough to obviate an anterior compressive bow wave that might physically disperse small prey and/or warn them of an approaching whale. Flow experiments (Werth, 2004, Werth, 2013 using pressure transducers and videorecording of particles and prey (Werth, 2012) have confirmed that these limited yet real pressure effects in laboratory settings (Figure 7), and tantalizing photographs and video recordings of whales foraging at sea (Werth and Potvin, 2016;Werth and Crompton, 2023) have likewise supported conclusions of Bernoulli and Venturi effects.…”
Section: Flow-dependent Porosity Determined By Varying Parametersmentioning
confidence: 58%
“…In addition to laterally supporting and constraining the baleen racks, the lips may be especially important in generating and modifying flow regimes (Werth et al, 2018a;Werth et al, 2019b); their positioning should be the focus of further flow experiments and field observations. The balaenid tongue may preferentially direct flow toward either rack (Werth, 2007;Werth and Crompton, 2023); it also, without moving, sets up a flow regime that channels flow toward each rack (Potvin and Werth, 2017;. Balaenids typically swim at about 0.7-1.0 m/s when filtering prey (van der Hoop et al, 2019;.…”
Section: Baleen As Metafilter With Structural Complexity and Variabilitymentioning
confidence: 99%
See 3 more Smart Citations